Os valores expressivos dos afixos na Norma Urbana Culta de São Paulo - Bacheschi, Celso Antônio (2006)
The corpus of this work are recordings made by the NURC/SP Project, contained in three volumes of A Linguagem Falada Culta na Cidade de São Paulo. The expressive values of the affixes are analyzed in it. Most of the work is dedicated to the -inho suffix, because this is the most common expressive element of the recordings. In addition to the diminutive sense, -inho has acquired specially expressive others, among them values of intensification, attenuation, exactness, lack of doubt, depreciation, similarity, euphemism, exiguity and irony are identified. Initially, occurring as a form linked to nouns, the -inho suffix begins to bind itself to other class words like adjectives, adverbs, numbers, pronouns, verbs, interjections. In the analysis of the corpus, it is observed that the value that the suffix gives to the word can change according to the context. It is observed too that the -inho suffix occurs more often when the speakers are talking about matters as animals, children and food. It is noticed too that the suffix values change according to the type of inquiry. Other suffixes analyzed are -ento, -eco, -ice, -eiro, -ado, -ão, -aço, -esco, -imo and -eria (-aria). Among them, we observe mainly pejorative, intensifying and collective values. The expressive prefixes have intensifying value. The presence of those expressive elements is used to measure the degree of formality of the inquiries. As theoretical referential, concepts of Stylistics, Sociolinguistics and Conversation Analysis were utilized